OPTIMIZATION OF CURCUMIN ENCAPSULATION FORMULA WITH CHITOSAN AND ALGINATE USING SIMPLEX LATTICE DESIGN AND ITS EFFECT ON ANTIOXIDANT ACTIVITY - Wiratantri, Fitra Indah; Peranginangin, Jason Merari; Sulaiman, Teuku Nanda Saifullah (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
Curcumin is known to enhance the performance of antioxidant serums, such as superoxide dismutase (SOD). However, curcumin is prone to degradation when exposed to sunlight, necessitating the use of encapsulation technology to protect it from chemical degradation and improve its dispersibility. Biopolymers like chitosan and alginate are commonly used as encapsulation materials. This study aimed to determine the ideal concentrations of chitosan and alginate for curcumin encapsulation and evaluate its antioxidant activity. The optimal formulation was identified using Design Expert software version 13 with a Simplex Lattice Design. Encapsulation was carried out through the ionic gelation method, and the curcumin encapsulates were evaluated for encapsulation efficiency, particle size, zeta potential, and antioxidant activity. The optimal formulation was found to be 1.35% chitosan and 2.145% alginate, achieving an encapsulation efficiency of 71.85%, a particle size of 551.1 nm, a zeta potential of -46 mV, and strong antioxidant activity with an IC50 value of 36.32 ppm. In conclusion, the Simplex Lattice Design method successfully optimized the formulation. Chitosan increased particle size, while alginate enhanced encapsulation efficiency. The antioxidant activity was minimally affected by encapsulation, as most curcumin was retained in the droplets. The zeta potential value confirmed the stability of the encapsulate.